Gerakan Peduli Masyarakat Melalui Pemberian Sembako dan Makanan di Kawasan Ngingas - Ernawati Ernawati; Nurul Layli; Rahayu Mardikaningsih; Didit Darmawan; Laili Mas Ulliyah Hasan (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Community outreach activities through the distribution of basic necessities and food were carried out in Ngingas Village. This movement was carried out because there were several underprivileged communities, so the role of students here was to distribute aid to ease their economic burden. This community service activity used the Participatory Learning and Action (PLA) method, a participatory learning and action method that is more often used in the context of community development and social projects. First, it began with the identification of problems and needs and the factors causing them, which were social inequality. After that, planning for the community service movement was carried out. The main objectives of this movement are to foster empathy among students in helping underprivileged communities, enhance solidarity among fellow students, and alleviate the economic burden of underprivileged communities. The results of this community service activity show that the PLA method can foster community involvement in this movement, so that this assistance is not seen as a show of generosity, but rather as a means of promoting mutual welfare and alleviating their economic burden.